Exhaust Emission Analysis on Motorcycle with Fuel and Gasoline Mixture of H2O Electrolysis - Arwati, I Gusti Ayu; Syamsul, Nurato; Izzati, Titia (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2017)
In this study, researchers used a type of motor 4 stroke 125 cc Suzuki Shogun brands with the year of manufacture 2010. Data collection exhaust emission test performed when the motor before and after wear electrolytes with various mixtures of electrolyte. Data were taken by the engine rotation changes from 1,000 RPM to 4,000 RPM. The highest yield for CO occurred at 4000 RPM with an electrolyte mixture of distilled water and 1 ½ tablespoons of KOH with a value of 1.04%. While the lowest CO occurred at 3,200 RPM when the motor was not used electrolysis with a value of 0.07%. For HC was highest at 1,000 RPM when the motor was not used electrolysis the value of 382 ppm. While the lowest occurred in HC 4,000 RPM with a mixture of distilled water and KOH electrolyte ½ tablespoons of as much as 20.33%. The highest value of CO2 was in the second electrolyte mixture, 8.2%. It was the first mixture between KOH electrolyte and distilled water. In the other hand, the lowest value of CO2 valuewas around 4.1%. It happened for the second time mixture while the motor electrolysis only distilled water and electrolytes itself.